Pembangunan Ekowisata Melalui Konsep Ekonomi Kreatif Berbasis Seni dan Budaya - Ivana Grace Sofia Radja; Leo Riski Sunjaya (Kajian Ekonomi dan Akuntansi Terapan, 2024)
In modern times, economic development has become the most important part of increasing economic growth in Indonesia, through the creative economy. New breakthroughs are needed in the field of ecotourism based on arts and culture. This research was conducted in the colorful village of Kalilo in Banyuwangi, where environmental conditions that are economically and socially unfavorable can transform these deficiencies into potential for sustainable development. By maximizing aspects of talent, tolerance and technology as well as instilling education, especially nationalist education, in the development of arts and culture in the village. The method used is descriptive qualitative based on Richard Florida's theory with the 3T concept (Talent, Tolerance, Technology). The results of the research that has been carried out have found that the use of the 3T concept from Richard Florida is able to dissect several aspects such as the condition of the people of Kalilo Village which is compact with a high level of creativity and is able to improve the economy of the surrounding community.